Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Literasi Sains pada Materi Ekosistem - Fadlila, Shafira Nur; Paujiah, Epa; Solikha, Maratus; Hadiansah, Hadiansah; Cahyanto, Tri (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to develop a Student Worksheet (LKPD) based on scientific literacy on the topic of ecosystems, assess its feasibility, and gather teacher feedback on the developed LKPD. The research employed a Research and Development (R&D) which includes three stages: Analyze, Design, and Develop. Data collection techniques involved a preliminary study through interviews to obtain initial information. The developed LKPD was then validated through expert validation questionnaires, readability tests by teachers and students, and student response questionnaires. The subject of this research was the scientific literacy-based LKPD, with participants consisting of one biology teacher and 15 tenth-grade students from MAN 1 Kota Bandung. The feasibility of the LKPD was assessed by two experts: a subject matter expert and a media expert. Data analysis was conducted using a Likert scale based on predetermined assessment criteria. The results showed that the material feasibility scored 85.33% with a